2019
DOI: 10.1016/j.drugalcdep.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Change in alcohol and other drug use during five years of continuous opioid substitution treatment

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…13 A recent publication from the English National Drug Treatment Monitoring System (NDTMS) reported that 39% of heroin users receiving OAMT were using alcohol at 5-year follow-up. 14 Of those using alcohol, 17.1% had "continued high-level alcohol use", 49.4% "continued low-level", 0.9% "increasing" and 17.6% "decreasing alcohol use". In Australia, at 2-year follow-up, decreases in heroin use were not associated with increases in other licit or illicit substance use.…”
Section: Introductionmentioning
confidence: 99%
“…13 A recent publication from the English National Drug Treatment Monitoring System (NDTMS) reported that 39% of heroin users receiving OAMT were using alcohol at 5-year follow-up. 14 Of those using alcohol, 17.1% had "continued high-level alcohol use", 49.4% "continued low-level", 0.9% "increasing" and 17.6% "decreasing alcohol use". In Australia, at 2-year follow-up, decreases in heroin use were not associated with increases in other licit or illicit substance use.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of alcohol after crack was related to a reduction in paranoia and craving, this strategy, identified by people who use crack as a way of diminishing the negative effects of crack (as it has been observed also with the use of marijuana [ 14 , 35 , 41 ], may stimulate a desire for crack, therefore inciting crack craving. Thus, alcohol might induce a vicious consumption circle of the two substances, contributing to a greater risk of alcohol and crack dependence [ 42 ], overdose [ 43 ], and other health damages caused by the use of crack cocaine [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another factor may involve behavioral or personality characteristics of individuals with OUD. In the longitudinal trajectory analysis of substitution therapy (Eastwood et al, 2019), those categorized into a "continued high-level heroin use" trajectory category also were more likely to use alcohol and crack than those in other trajectory categories. Such results suggest that alcohol use may be one of the multiple drugs of misuse in a subset was not the alcohol use per se that increased problems, but rather the fact that alcohol use was associated with an increased likelihood of sedative use, and that sedative use led to poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal trajectory analysis of 7,717 patients receiving methadone or buprenorphine substitution therapy found that among the 50% of the sample with significant levels of alcohol consumption, about a third increased, a third decreased, and a third remained unchanged in the frequency of alcohol intake over a 5‐year period (Eastwood et al, 2019). Other studies have shown decreases (Caputo et al, 2002; Nava et al, 2008) or no change in alcohol use (Klimas et al, 2016, 2018) with methadone or buprenorphine treatment, although an older literature had reported treatment‐related increases in alcohol use (Anglin et al, 1989; Gelb et al, 1978; Simpson & Lloyd, 1978).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation